2020
DOI: 10.1039/d0nr01960g
|View full text |Cite
|
Sign up to set email alerts
|

In situ X-ray emission and high-resolution X-ray absorption spectroscopy applied to Ni-based bimetallic dry methane reforming catalysts

Abstract: The effect of cobalt on the catalytic activity of a NiCoO dry methane reforming catalyst was investigated by in situ XES and HERFD XAS. Co is shown to hamper the reduction of the Ni in the NiCoO catalyst by modulation of its electronic structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…However, the XPS approach becomes impossible for supported dilute alloy catalysts in which the dopant concentration is <1% as XPS is not a trace element technique (∼100 ppm in the case of NiAu/SiO 2 SAA), a concentration regime at which HERFD XANES provides analyzable information. Similar evidence of the electronic structure modulation of Ni by the presence of another metal has been demonstrated by DeBeer and co-workers in Ni 3 Co 1 alloys, as evidenced via HERFD XANES analysis, as well as by the Bao group on Ni 1 Pt 4 alloys based on conventional XANES measurements; however in both cases considerably higher concentrations of Ni were present in the samples. , …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…However, the XPS approach becomes impossible for supported dilute alloy catalysts in which the dopant concentration is <1% as XPS is not a trace element technique (∼100 ppm in the case of NiAu/SiO 2 SAA), a concentration regime at which HERFD XANES provides analyzable information. Similar evidence of the electronic structure modulation of Ni by the presence of another metal has been demonstrated by DeBeer and co-workers in Ni 3 Co 1 alloys, as evidenced via HERFD XANES analysis, as well as by the Bao group on Ni 1 Pt 4 alloys based on conventional XANES measurements; however in both cases considerably higher concentrations of Ni were present in the samples. , …”
Section: Resultssupporting
confidence: 81%
“…Similar evidence of the electronic structure modulation of Ni by the presence of another metal has been demonstrated by DeBeer and co-workers in Ni 3 Co 1 alloys, as evidenced via HERFD XANES analysis, as well as by the Bao group on Ni 1 Pt 4 alloys based on conventional XANES measurements; however in both cases considerably higher concentrations of Ni were present in the samples. 64,65 While little experimental data exist for charge transfer in SAAs, the electronic structure of Ni atoms in NiAu SAAs has been examined theoretically. 66 Specifically, the d states of Ni atoms in a Au(111) host were computed by Thirumalai and Kitchin, and their results revealed a very narrow electronic state near the Fermi level indicative of a lack of hybridization of the Ni d states with the host Au.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…117 Many reports have described the existence of an optimal Co/Ni ratio, but the value varies depending on the catalyst. In addition, in situ XPS, 116 and in situ scanning transmission X-ray microscopy (STXM) 118,119 studies have been conducted recently.…”
Section: Addition Of the Base Metal To Ni Catalystsmentioning
confidence: 99%
“…Askari et al 118,119 investigated Ni-Co alloy catalysts using the technique of in situ STXM and showed a different result of in situ XPS study by Wu et al 116 Askari et al 118 first prepared NiCoO x /γ-Al 2 O 3 catalyst by the modified reverse micellar method, of which compositions are determined by EDX as 56.4 atom% of O, 1.1 atom% of Co, 9.2 atom% of Ni, and 33.3 atom% of Al. Later, STXM studies of NiCoO x /γ-Al 2 O 3 catalyst were conducted under Ar, 5%H 2 /Ar, and DRM atmosphere.…”
Section: Published a Minireview On Ni-fe Alloy Catalysts For Reformin...mentioning
confidence: 99%
“…Besides XANES and EXAFS, so XAS is also efficient in the detection of chemical states, orbital hybridization and atom-specic local environments of SACs. [63][64][65] It is also demonstrated that establishing traditional characterization methods based on synchrotron-radiation light can improve their data quality and reliability to a large extent. For instance, synchrotron radiation XPS, one of the most important surface-sensitive characterization methods, can obtain the surface information of catalysts with high energy resolution.…”
Section: Introductionmentioning
confidence: 99%